2017
DOI: 10.1002/mds.27198
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in progressive supranuclear palsy is associated with tau burden

Abstract: Background Cognitive impairment is one of the core features of progressive supranuclear palsy. This study aimed to clarify the profile of cognitive impairment and its underlying pathology in progressive supranuclear palsy. Methods We retrospectively reviewed medical records to evaluate the pattern and severity of cognitive impairment in 121 autopsy-confirmed progressive supranuclear palsy patients. A subset of 37 patients underwent neuropsychological evaluation as part of their clinical work-up. The burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The dementia and frontal symptoms, the most common features in PSP-F, were associated with earlier death [26,31]. A recently published study found cognitive impairment in PSP, especially executive dysfunction, was associated with severity of PSP-related tau pathology in autopsy-confirmed PSP patients, which might explain the association with poorer prognosis [32]. After excluding PSP-F and PSP-FOG, we found that a trend for the association of PSP-P with a longer survival.…”
Section: Discussionmentioning
confidence: 97%
“…The dementia and frontal symptoms, the most common features in PSP-F, were associated with earlier death [26,31]. A recently published study found cognitive impairment in PSP, especially executive dysfunction, was associated with severity of PSP-related tau pathology in autopsy-confirmed PSP patients, which might explain the association with poorer prognosis [32]. After excluding PSP-F and PSP-FOG, we found that a trend for the association of PSP-P with a longer survival.…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemistry for phospho-tau (CP13, mouse monoclonal, 1:1000, from Dr. Peter Davies, Feinstein Institute, North Shore Hospital, NY) was performed using a DAKO Autostainer (Universal Staining System, Carpinteria, CA) to establish the neuropathological diagnosis of CBD [10]. The severity of tau pathology, including NFTs, pretangles, coiled bodies, astrocytic plaques, and threads was graded semi-quantitatively on a four-point scale (0 = absent, 1 = mild, 2 = moderate, 3 = severe) by an experienced neuropathologist (DWD) in 21 brain regions: inferior temporal gyrus, superior frontal gyrus, motor cortex, caudate, globus pallidus, basal nucleus, hypothalamus, ventral thalamus, subthalamic nucleus, thalamic fasciculus, red nucleus, substantia nigra, oculomotor complex, midbrain tectum/superior colliculus, locus coeruleus, pontine tegmentum, pontine base, medullary tegmentum, inferior olivary nucleus, dentate nucleus, and cerebellar white matter [28]. The regional tau burden was defined as the sum of scores for all lesion types in each brain region (range: 0–12) [28].…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the tau burden, digital image analysis was performed in select brain regions [28]. CP13-stained sections of the pons, medulla, and cerebellar hemisphere were scanned on the ScanScopeXT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in AD, there is evidence for tau oligomers driving neurodegeneration in PSP . Furthermore, the burden of tau pathology is positively associated with the degree of cognitive impairment in PSP cases . Pick's disease is a rare form of dementia originally characterized by Arnold Pick in the late 1800s.…”
Section: The Role Of Tau In Ad and Ftld‐taumentioning
confidence: 99%